Prospective Evaluation of Germline Alterations in Patients With Exocrine Pancreatic Neoplasms. (28th February 2018) - Lowery, Maeve A; Wong, Winston; Jordan, Emmet J; Lee, Jonathan W; Kemel, Yelena; Vijai, Joseph; Mandelker, Diana; Zehir, Ahmet; Capanu, Marinela; Salo-Mullen, Erin; Arnold, Angela G; Yu, Kenneth H; et al.
Abstract: Background: Identification of pathogenic germline alterations (PGAs) has important clinical and therapeutic implications in pancreas cancer. We performed comprehensive germline testing (GT) in an unselected prospective cohort of patients with exocrine pancreatic neoplasms with genotype and phenotype association to facilitate identification of prognostic and/or predictive biomarkers and examine potential therapeutic implications. Methods: Six hundred fifteen unselected patients with exocrine pancreatic neoplasms were prospectively consented for somatic tumor and matched sample profiling for 410–468 genes. GT for PGAs in 76 genes associated with cancer susceptibility was performed in an "identified" manner in 356 (57.9%) patients and in an "anonymized" manner in 259 (42.1%) patients, using an institutional review board–approved protocol. Detailed clinical and pathological features, response to platinum, and overall survival (OS) were collected for the identified cohort. OS was analyzed with Kaplan-Meier curves. Results: PGAs were present in 122 (19.8%) of 615 patients involving 24 different genes, including BRCA1/2, ATM, PALB2, and multiple additional genes associated with the DNA damage response pathway. Of 122 patients with germline alterations, 41.8% did not meet current guidelines for GT. The difference in median OS was not statistically significant between patients with and without PGA (50.8 months, 95% confidence interval = 34.5 to not reached, two-sided P = .94). Loss of heterozygosity was found in 60.0% of BRCA1/2 . Conclusions: PGAs frequently occur in pancreas exocrine neoplasms and involve multiple genes beyond those previously associated with hereditary pancreatic cancer. These PGAs are therapeutically actionable in about 5% to 10% of patients. These data support routinely offering GT in all pancreatic ductal adenocarcimona patients with a broad panel of known hereditary cancer predisposition genes.